Pengaruh Berbagai Kecambah Kacang-Kacangan Lokal sebagai Bahan Dasar Meat Analog terhadap Sifat Fisik (Tekstur), Kesukaan dan Rasio Arginin/Lisin - Bayu Kanetro; Sri Hartati Candra Dewi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
The aims of this research were to determine the best of local legume sprout as raw material of meat analog, based on its texture, sensory (preference properties), and the ratio of arginine/lysine, compared to meat analog from soybean. Meat analogs were made of protein of local legumes sprout, which were velvet beans, cowpeas, and winged beans that had been germinated for 48, 36 and 24 hr respectively. The protein of velvet beans, cowpeas, and winged beans sprout for meat analog production were extracted at pH 9 and precipitated at pH 4, 5, and 5 respectively. Hence their products were analyzed the texture, the sensory properties (the hedonic scales of color, texture, odor, taste, and overall), and the ratio of arginine/lysine. The characteristics of meat analog from the legumes sprout were compared to meat analog from soybean for determination of the best legume sprout as raw material of meat analog. The result of this research showed the properties of meat analog from winged bean and cowpeas sprouts were better than velvet beans sprout. The meat analog from soybean was still better than meat analog from the local legumes sprout, especially its texture. The arginine content, that was known as hypocholesterolemic and hypoglycemic component, of meat analog from cowpeas sprout was lower than meat analog from soybean, but its ratio of arginie/lysine was not signiﬁ cantly different. While the ratio of arginine/lysine of meat analog from the other legumes sprout were lower than meat analog from soybean. Therefore the meat analog from cowpeas sprout was chosen as the best product and was potential as functional food especially for reducing blood cholesterol.ABSTRAKTujuan penelitian ini adalah untuk menentukan jenis kecambah kacang-kacangan lokal terbaik sebagai bahan baku kedelai berdasarkan tekstur, sifat sensoris, dan rasio arginin/lisin dibandingkan meat analog dari biji kedelai. Meat analog dibuat dari protein berbagai kecambah kacang-kacangan lokal, yaitu kacang kara benguk, tunggak, dan kecipir yang dikecambahkan berturut-turut selama 48, 36 dan 24 jam. Protein kecambah kacang kara benguk, tunggak dan kecipir untuk memproduksi meat analog diekstraksi pada pH 9, selanjutnya dipresipitasi berturut-turut pada pH 4, 5, dan 4. Produk-poduk yang diperoleh dianalisis tekstur, sifat sensoris (tingkat kesukaan terhadap warna, tekstur, bau, rasa dan keseluruhan), dan rasio arginin/lisin. Karakteristik meat analog dari berbagai kecambah kacang-kacangan lokal tersebut dibandingkan dengan meat analog dari biji kedelai untuk menentukan jenis kecambah terbaik sebagai bahan dasar meat analog. Hasil penelitian menunjukkan bahwa karakteristik meat analog kecambah kacang tunggak dan kecipir lebih baik dibandingkan meat analog dari kecambah kara benguk. Meat analog dari biji kedelai masih lebih baik daripada meat analog dari kecambah kacang-kacangan, khususnya teksturnya. Kandungan arginin yang diketahui sebagai komponen hipokolesterolemik dan hipoglisemik pada meat analog kecambah kacang tunggak ternyata lebih rendah daripada meat analog kedelai, tetapi rasio arginin/lisinnya tidak berbeda nyata. Sedangkan rasio arginin/lisin meat analog dari kecambah kacang-kacangan lainnya lebih rendah daripada meat analog dari biji kedelai. Oleh karena itu meat analog dari kecambah kacang tunggak dipilih sebagai produk terbaik dan berpotensi sebagai pangan fungsional utamanya untuk menurunkan kolesterol darah.